Effectiveness of Blended Learning Model-Based on “Kutub al-Tis’ah” Application in Improving Students’ Critical Thinking in Hadith Study Courses - Channa, Lilik (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
This study compares the enhancement of students’ critical thinking abilities between those who utilise the Blended Learning model based on Kutub al-Tis’ah and those who adhere to a conventional learning methodology. A quasi-experimental method with purposive sampling was employed, with two classes from the Architecture Study Program at the State Islamic University of Sunan Ampel Surabaya in 2020/2021 serving as samples. The experimental group was instructed using the blended learning model, while the control group was taught using conventional methods. The results of the post-test demonstrated that the experimental class exhibited significantly higher scores (with an average of 90.32 and a variance of 6.799) than the control class (with an average of 65.81 and a variance of 5.872). The results of the statistical tests, including those for normality (Kolmogorov-Smirnov and Shapiro-Wilk) and homogeneity (Levene), demonstrated that the data from both groups were normally distributed and homogeneous. A p-value of 0.00, less than 0.05, indicated that the null hypothesis should be rejected, demonstrating that the blended learning model effectively enhances critical thinking skills in Hadith Studies courses.